Urban-rural differences of free activities in children of age 11-14 - Brestovci, Shqipe Bajcinca; Morina, Besnik; Berisha, Mentor (Journal of Education, Health and Sport, 2020)
Objectives: The problem of the research is to investigate the situation of free activities of primary school students in urban and rural areas in Kosovo. The subject of the research is male and female third level elementary school students (grades 6, 7, 8, 9) in urban and rural areas. In accordance with the object and the problem defined in this research, the main purpose of the research is also defined. The main purpose of this research is to determine what children do during their free time, as well as to look at the differences between children in urban and rural areas. Methods: The research was conducted in a sample consisting of 413 boys and girls (11 – 14) attending elementary school. The total sample includes 413 respondents, 202 boys and 211 girls. The sample is divided into the following sub-samples: 115 eleven year old male and female students, 144 twelve year old male and female students, 97 thirteen year old male and female students, 57 fourteen year old male and female students. The research material was collected in 2017. To assess what the students do more in their spare time a questionnaire called "My Lifestyle" was used. Results: Research results show that the most frequent forms of leisure time spending are: listening to music, meeting friends, playing with friends, reading books and watching videos/TV. The obvious reason for this may be the lack of access to sports equipment and facilities. Conclusion: This research shows that the level of wealthier (not very high both in households and in the whole country) can have an impact on the choice of activities undertaken by young people. Undoubtedly, social and cultural as well as traditional factors also have a great influence in the way of spending free time as can be seen in the case of this study.